Good Governance dalam Islam: Kepemimpinan dalam Islam - Alifah Nur Sulistiawati; Rahma Lia Amanda; Tiara Rahmawati; Puspita Anjar Any (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Leadership in Islam, highlighting its ethical and pragmatic foundations. Good governance in Islam is deeply rooted in the principles of al-amanah (trustworthiness) and al-'adalah (justice), which are not only administrative norms but also moral and spiritual obligations. Leadership in Islam is understood as a sacred mandate carried out by the caliph, imam, and ulil amri, each of which has spiritual, moral, and executive dimensions. Prophetic qualities in the form of shidq (honesty), amanah (trustworthiness), fathonah (intelligence/wisdom), and tabligh (accurate delivery/communication) are ethical foundations that are inseparable from effective leadership. The qualifications of a Muslim leader are very diverse, ranging from faith, noble morals, justice, knowledge, courage, and devotion in public service. The way of government of the Prophet Muhammad SAW was inclusive and tolerant. The period of the Khulafaur Rasyidin (Abu Bakar, Umar, Uthman, and Ali) shows how government administration developed, even though it was full of challenges. This history proves that the principles of good governance in Islam remain strong, even in difficult times.